Women's Representation To Establish Anti-Corruption In The Village Government Of Kotaraja, Hulu Sungai Utara - Lena Hanifah; Dadang Abdullah; Nor Ismah (Scholar Center, 2024)
The representation of women in village governance, particularly in the Village Consultative Body (BPD), is mandated by Law Number 6 of 2014 concerning Villages. Fulfillment of this mandate becomes a subject of debate when the role is merely symbolic to meet the quota of women in village governance. In this context, the method employed is qualitative analysis, utilizing a socio-legal approach that highlights the complexity of social and legal dynamics influencing women's representation in the Village Consultative Body. The role of female representatives is crucial in enhancing the welfare of rural communities, simultaneously contributing to the realization of a corruption-free village. Additionally, they possess a unique closeness and empathy towards the issues faced by women in their villages, enabling them to gain the trust of the community. Residents of Kota Raja Village also perceive female candidates as being corruption-free and capable of fulfilling their duties and responsibilities, thereby earning trust from their respective neighborhood associations (RT - Rukun Tetangga). This situation is evident in the increased representation of women in the governance of Kota Raja Village, especially in the Village Consultative Body. In the newly elected Village Consultative Body for the period 2023-2029, 50% of its members are women, up from 44%. This figure demonstrates the positive perception of Kota Raja Village residents regarding the importance of women's representation in village governance. However, doubts persist regarding whether women's representation is merely symbolic and whether it reflects sincere efforts to empower women in village governance. Nonetheless, this raises further questions about the skills of female representation in addressing the complex issues faced by rural communities.and application within the framework of Indonesian law.